Identifying Pre-hypertensives in the Community: At Risk Approach for Prevention of Hypertension - Singh, Pallavi; Saxena, Vartika (Indian Journal of Community Health, 2023)
Introduction: Pre-hypertension is a borderline health state of increased blood pressure (BP) that falls short of the measurable parameters at which surveillance and/or therapy would be required. The approach of identifying people “At Risk” of developing hypertension can be more cost-effective and feasible for applying lifestyle interventions. Objectives: The objective of the present study is to find the prevalence of pre-hypertensives and associated bio-socio-demographic factors Materials and Methods: A cross-sectional study was conducted among 1946 participants aged 19 years and more in the Doiwala block of Dehradun, Uttarakhand. Multistage sampling was used to arrive at desired sample size. A pre-validated, structured questionnaire was used for data collection. The questionnaire included information on the socio-demographic profile (age, sex, education etc.), awareness about hypertension and its associated risk factors. Statistical Analysis: The chi-square test was used to compare proportions and draw inferences. Results: 958 (49.2%) study participants out of a total 1946 were found to be pre-hypertensives. A statistically significant association was found between pre-hypertension and factors such as male gender, age, education, occupation and waist-hip ratio. (p<0.05) Conclusion: It is recommended that identification on the pre-hypertensive group and subjecting them to lifestyle modification could be a fruitful strategy for preventing them from becoming hypertensive.